Advances in Mechanisms of Renal Fibrosis - David J. Nikolic-Paterson (Frontiers Research Topics, 2018)
Scarring of the glomerular and tubulointerstitial compartments is a hallmark of progressive kidney disease. Renal fibrosis involves a complex interplay between kidney cells, leukocytes and fibroblasts in which transforming growth factor-β (TGF-β) plays a key role. This eBook provides a comprehensive update on TGF-β signalling pathways and introduces a range of cellular and molecular mechanisms involved in renal fibrosis both upstream and downstream of TGF-β. The wide variety of potential new targets described herein bodes well for the future development of effective therapies to tackle the major clinical problem of progressive renal fibrosis.